Captain Grey's Gambit : a novel - Gelernter, J. H. (New York : W W norton & company, 2022)
It's December 180, and a French invasion fleet is poised to cross the Channel and storm the beaches of southern England. A member of Napoleon's inner circle--disaffected by Napoleon's creeping tyranny--contacts the British naval intelligence service in hopes of defecting to London. His escape plan calls for a rendezvous at an international chess tournament in Frankfurt--a rare opportunity for him to travel outside France. Naval intelligence sends its top man--and best chess player--Captain Thomas Grey, to orchestrate the Frenchman's escape to England. But Grey's mission changes dramatically when the defector demands that his pro-Napoleon daughter come with him--expecting Grey to act not just as escort but kidnapper.
Keywords: Defectors France Fiction; Chess Fiction; Action and adventure fiction